2008
DOI: 10.1016/j.dendro.2007.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Wood anatomical changes in roots of European ash (Fraxinus excelsior L.) after exposure

Abstract: Global changes have distinct influence on fluvial processes in torrents causing erosion on slopes and riverbanks even in forested areas. Continuous as well as discontinuous erosion of riverbanks covered by trees frequently results in destabilisation and finally cause the trees affected to tip over. These uprooted trees may lead to a blockage of the river and, in the case of a collapse of the resulting dam, resulting in severe flooding or even debris-flow surges. Dating the time of root exposure along riverbank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…The morphology of wood in roots changes when exposed to the air (probably a mechanical response) with new wood usually having smaller vessels (Hitz et al . ). Leaf area to root biomass ratio increases with decreasing irradiance (36% down to 4% full sunlight), but more so in Acer pseudoplatanus than ash (Barigah et al .…”
Section: Structure and Physiologymentioning
confidence: 97%
“…The morphology of wood in roots changes when exposed to the air (probably a mechanical response) with new wood usually having smaller vessels (Hitz et al . ). Leaf area to root biomass ratio increases with decreasing irradiance (36% down to 4% full sunlight), but more so in Acer pseudoplatanus than ash (Barigah et al .…”
Section: Structure and Physiologymentioning
confidence: 97%
“…Abrupt suppression of growth as well as tangential rows of traumatic resin ducts are now being used to recognize anomalies that reflect erosion in the root zone. As a further result of the loss of edaphic cover, that is, the uppermost soil horizons, roots produce earlywood tracheid cells and vessels with lumina of significantly reduced width (Gärtner et al , ; Bodoque et al , ; Hitz et al , ). Corona et al () recently demonstrated that the reduction of cell lumina starts to occur before the root is exposed and as soon as the soil mantle covering the uppermost segment of the root is reduced to about 30 mm.…”
Section: Current Approaches To Landscape Modeling Effects Of Climatimentioning
confidence: 99%
“…diffuse-porous species drastically increase vessel size after stem burial (Beakbane, 1941;Sigafoos, 1964;Fayle, 1968;Friedman et al, 2005), ring-porous species exhibit decreases in earlywood-vessel size (Knowlson, 1939;Cournoyer and Bégin, 1992;Friedman et al, 2005;Den Ouden et al, 2007). In addition, ring-porous species show the tendency to appear diffuse porous, or root like, after burial and shift back to ring-porous after exposure (Fayle, 1968;Cournoyer and Bégin, 1992;Den Ouden et al, 2007;Hitz et al, 2008).…”
Section: Introductionmentioning
confidence: 94%